Design and Photocatalytic Evaluation of CdO–ZnO–Co3O4 Ternary Nanocomposite Synthesized by Co-precipitation Method (Thamar University Journal of Natural & Applied Sciences, 2025)
A CdO–ZnO–Co3O4 ternary nanocomposite was synthesized via the co-precipitation method. Transmission electron microscopy (TEM) confirmed the spherical morphology of the nanoparticles, with average particle sizes of 60.8 nm (CdO), 51.8 nm (ZnO), 33.3 nm (Co3O4), and a significantly reduced size of 13.82 nm for the nanocomposite. Crystallographic analysis revealed cubic structures for CdO and Co3O4, and a hexagonal structure for ZnO. Elemental composition was validated through total reflection X-ray fluorescence (TXRF). Diffuse reflectance spectroscopy (DRS) was employed to assess the optical properties, including reflectance and band gap energies. CdO and ZnO exhibited direct band gaps of 2.0 eV and 3.15 eV, respectively, whereas Co₃O₄ presented two band gap transitions at 1.0 eV and 1.43 eV, corresponding to charge transfers from O²⁻ to Co³⁺ and Co²⁺ ions. The ternary nanocomposite demonstrated a narrowed band gap of 1.4 eV. Photocatalytic testing against methylene red (MR) dye under UV irradiation showed a notable degradation efficiency of 33.5% within 30 minutes. These results suggest that the CdO–ZnO–Co3O4 nanocomposite holds strong potential for application in wastewater treatment